Speech language pathologists’ attitudes on bilingual practices for children with autism in India: A qualitative study - Kaluva Bindu Sree; Sebastian Padickaparambil; Shivani Tiwari (PLoS ONE, 2026)
The present study, aimed to investigate SLPs’ attitude regarding bilingual practices in children with autism. We conducted in-depth telephonic interviews on 13 SLPs working with autistic children in India having at least 2 years of work experience. The data obtained were subjected to stepwise inductive thematic analysis. Results of the study displayed five themes, viz. SLP’s opinion of monolingual vs. bilingual approaches in children with autism, Bilingual Practices for children with autism, Factors explaining the choice of language, Suggestions for parents of children with autism and future SLPs, and Need and scope for bilingual practice. Results of the study indicated SLP’s divergent attitude towards bilingual practices in children with autism, factors explaining the choice of language, such as lack of culturally appropriate assessment tools, and limited strategies for addressing parental concerns. These findings have implications to address awareness of evidence based bilingual practices in SLPs for children with ASD in multilingual settings, development of practice guidelines and standardized tests in underdeveloped languages. Furthermore, there is a need to educate and address concerns of parents and families of autistic children regarding bilingual approach.